Scientometrics - Jibu, Mari; Osabe, Yoshiyuki (IntechOpen, 2018)
Technological change is one of the greatest issues in the modern world. As the world faces societal challenges, e.g., climate challenges, aging problem, and energy security, technology will contribute to new or better solutions for those problems. New technologies take time to develop and mature; moreover, they tend to be born in the gaps of multiple technology fields; therefore, early detection of emerging technological concepts across multiple disciplines will be a very important issue. Our goal seeks to develop automated methods that aid in the systematic, continuous, and comprehensive assessment of technological emergence using one of the major foresight exercises, scientometrics. There is now a huge flood of scientific and technical information, especially scientific publications and patent information. Using the information patterns of emergence for technological concepts has been discovered and theories of technical emergence have been also developed in several years. We have been developing visualization tools in which thousands of technical areas have been interacted with each other and evolved in time. Several indicators of technical emergence have been improved by universities, international organizations, and funding agencies. This book intends to provide readers with a comprehensive overview of the current state of the art in scientometrics that focuses on the systematic, continuous, and comprehensive assessment of technological emergence.